New version of derivative consequence argument and response to objections - B. V. Faul (Омский научный вестник: Серия "Общество. История. Современность")
In this paper, I respond to the objections and comments, which are raised by D. Razeev, T. Demin, and M. Sekatskaya. I provide a new formulation of the argument, which avoids all the problems mentioned by these philosophers in their papers and at the conferences